HUBUNGAN ANTARA KETERAMPILAN SOSIAL DAN PENGGUNAAN GADGET SMARTPHONE TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI 9 MALANG - Dewanti, Tania Clara; Widada, Widada; Triyono, Triyono (citeus, 2024)
This study aims to determine the relationship between Social Skills and Use Gadgets Smartphone with Student Achievement SMA Negeri 9 Malang. This research is descriptive corelational. Total population of this study were 316 students with a total sample of 84 students. The sample selection using questionnaires and Likers scale and documentation in the form of report cards. Test requirements analysis using normality test and test linier. The analytical method used is multiple regression analysis. The results of this study indicate that: (1) There is a significant relationship between social skills and academic achievement obtained count r = 0.442> r table 5% = 0.312 and p = 0.000 <0.05. (2) There is a relationship between the use of gadgets smartphone with student achievement obtained count r = 0.425> r table 5% = 0.312 and p = 0.000 <0.05. (3) There is a positive relationship between social skills and use your smartphone gadgets and academic achievement, demonstrated the significant value which was 0.000 ≤ 0.05, which means that Ha value is accepted. Based on research, there are some suggestions to consider: (1) For the counselor, as a contribution and useful information to develop programs of Guidance and Counseling in particular in the field of counseling services social, about the counseling services of social skills and the use of gadgets smartphones to high school students in order to develop optimally. (2) Parents are expected to be able to monitor properly the development of children, as well as guiding and educating to improve child development. (3) For further research are expected next researcher to use this research as a reference or to examine additional data related to social skills and use your smartphone gadget with academic achievement.